2011
DOI: 10.1093/infdis/jir316
|View full text |Cite
|
Sign up to set email alerts
|

Deteriorating Pneumococcal-Specific B-Cell Memory in Minimally Symptomatic African Children With HIV Infection

Abstract: Invasive pneumococcal disease is a leading cause of human immunodeficiency virus (HIV)-associated mortality in sub-Saharan African children. Defective T-cell-mediated immunity partially explains this high disease burden, but there is an increased risk of invasive pneumococcal disease even in the context of a relatively preserved percentage of CD4 cells. We hypothesized that impaired B-cell immunity to this pathogen further amplifies the immune defect. We report a shift in the B-cell compartment toward an apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
5
27
0
Order By: Relevance
“…A shift in B cell populations has also been implicated in the increased susceptibility of HIV-infected children to pneumococcal disease. 42 Here, children with HIV were found to have reduced numbers of circulating mature, naïve and resting B MEM , with an over-representation of mature, activated B cells.…”
Section: -Valent Pneumococcal Polysaccharide Vaccine (Ppv-23)mentioning
confidence: 89%
“…A shift in B cell populations has also been implicated in the increased susceptibility of HIV-infected children to pneumococcal disease. 42 Here, children with HIV were found to have reduced numbers of circulating mature, naïve and resting B MEM , with an over-representation of mature, activated B cells.…”
Section: -Valent Pneumococcal Polysaccharide Vaccine (Ppv-23)mentioning
confidence: 89%
“…36 Response to the PCV vaccine is mostly mediated by B-cells; in this respect, depletion of B-cell subsets and pneumococcus-specific memory B-cells has recently been reported in HIV-1 infected African children with invasive pneumococcal disease despite a proportion of CD4 + T-cells being over 15%. 98 Therefore, results from these studies suggest that evaluating immune responses to pneumococcal vaccination in HIV-1 VZV belongs to the family of herpes viruses, therefore formation of varicella specific CD8 + T-cells is particularly important to prevent reactivation and infection following vaccination. In view of this, positive responses to vaccination in HIV-1 infected children have also been evaluated by varicella-specific lymphoproliferative assay (LPA) with stimulation indices (SI) above 3.…”
mentioning
confidence: 99%
“…In support of this, the number of publications reporting the set-up of new antigen-specific B-cell ELISpot is increasing in the literature. 36,98,122 Application of such methods may be beneficial for vaccine design not only for HIV-1 infected patients but also for patients with other primary and secondary immune diseases presenting with similar immune disorders.…”
mentioning
confidence: 99%
“…These observations support the hypothesis that HIV infection impacts upon acquired immunity in such a way as to affect the immune response to some pneumococcal serotypes more than others. In healthy individuals, serotype-specific IgG responses to PCV vary according to serotype, despite uniform T-cell responses to vaccine carrier protein [26]. It has been suggested that this may be a result of variations in B-cell repertoire [26].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, serotype-specific IgG responses to PCV vary according to serotype, despite uniform T-cell responses to vaccine carrier protein [26]. It has been suggested that this may be a result of variations in B-cell repertoire [26]. Reports from our own group and others have demonstrated alterations in B-cell phenotype in the context of HIV [2736], which can be related to both naturally acquired and vaccine-induced pneumococcal immunity [27,32,34].…”
Section: Discussionmentioning
confidence: 99%